2015
DOI: 10.1590/1516-635x1702181-190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascorbic Acid Injection in Incubated Eggs Submitted to Heat Stress on Incubation Parameters and Chick Quality

Abstract: Dose-dependent positive effects on hatchability and hatchling weight have been attributed to ascorbic acid (AA) when eggs were submitted or not to intermittent heat stress during incubation. Fertile breeder (Cobb®) eggs were used to determine if the pre-incubation injection of AA in ovo affects the incubation and hatchling quality of egg incubated under thermoneutral or intermittent heat stress conditions. Eggs were not injected or injected with 0, 2,4, or 6% AA/100µL water and incubated at continuous thermone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
5
19
0
1
Order By: Relevance
“…These results are consistent with the reported by Sgavioli et al (2015), who observed higher eggshell surface temperature in the second half of the incubation period of broiler eggs submitted or not heat stress during incubation and injected or not with vitamin C.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the reported by Sgavioli et al (2015), who observed higher eggshell surface temperature in the second half of the incubation period of broiler eggs submitted or not heat stress during incubation and injected or not with vitamin C.…”
Section: Discussionsupporting
confidence: 93%
“…Hatchability was increased by in-ovo injection with ascorbic acid (Ipek et al, 2004), L-arginine (Al-Daraji et al, 2012), and carbohydrates (Dong et al, 2013). However, hatchability was reduced by in-ovo injection with ascorbic acid (Sgavioli et al, 2015), organic trace minerals (Oliveira et al, 2015), glucose (Ebrahimnezhad et al, 2011), and glucose and magnesium (Salmanzadeh et al, 2012). In contrast, Bhanja & Mandal (2005), Nowaczewski et al (2012), Moore et al (1994), Shafey et al (2012), and Coskun et al (2014) reported that hatchability was not affected when eggs were injected with amino acids, vitamin C, hormones, carbohydrates, and pollen extract, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The use of 2% propolis and 3% propolis may be toxic for the embryo, particularly during these incubation ages. However, Nowaczewski et al (2012), Sgavioli et al (2015), Shafey et al (2012), and Ipek et al (2004) reported that in-ovo injection with vitamin C, ascorbic acid, carbohydrates, and glucose, respectively, had no significant effect on embryonic mortality. Chick body weight on d 10 and body weight gain were not affected by the in-ovo injection of propolis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding hatch time, chicks were hatched earlier (P>0.05) for eggs exposed to 41°C (377.88 hrs) by about 17.38 hrs compared with 37.5°C (395.26 hrs) this may be due to higher metabolic rate accompanied with increased respiration rate, resulting in decreased O2 supply and increased CO2 concentrations inside the egg which, accelerate hatch time (Everaert et al, 2007). Sgavioli et al, (2014) reported that the elevated temperature generally accelerated hatching time but this was not in concert with the development of the organs. With respect to the effect of AA treatments, data indicate that the rate of embryonic mortality was decreased remarkably due to treatment with ascorbic acid and thus increased hatching rate compared with the untreated group (Table 5).…”
Section: Embryonic Mortality Hatchability and Duration Of Incubationmentioning
confidence: 97%